Student Satisfaction to Service Quality of University’s Sports Centre: A Factor Analysis Approach - Misiran, Masnita; Md Yusof, Zahayu; Ibrahim, Adyda; Chong, Siow Hui; Baharin, Nur Fatiha; Hamid, Hairani (Penerbit Akademia Baru, 2017)
Student’s lifestyle should comprises of both academic and extracurricular activities as both activities have been proven to increase maturity and develop mental resilience in student’s general well-being. This article attempts to extract attributing factors that contribute to the satisfaction of Universiti Utara Malaysia (UUM)’s Sport and Recreation Centre (SRC) among students residing in campus. Questionnaires were developed and distributed among UUM students by using systematic sampling method. We will use descriptive statistics and factor analysis to analyse the collected data. The results of 374 questionnaires discovered that the contributing factors are Tangibles, Responsiveness, Reliability and Assurance. These four factors show significant relationship with the student satisfaction towards UUM SRC. These findings reinforce the need for UUM’s management to pay attention on the mentioned factors. In addition, this research can help the management to improve the service quality in UUM SRC by improving and increasing the reliability of the UUM SRC. Through these findings, the management can have a better understanding about what students need and improve the service quality in UUM SRC to satisfy the needs of students